2016
DOI: 10.1118/1.4963208
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound neuromodulation of cortical and subcortical brain structures using 1.9 MHz

Abstract: The motor movements and pupillary dilation observed in this study demonstrate the capability of FUS to modulate cortical and subcortical brain structures without inducing any damage. The variety of responses observed here demonstrates the capability of FUS to perform functional brain mapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 22 publications
(18 reference statements)
6
87
2
Order By: Relevance
“…Finally, adding further weight to the idea that US stimulation acts directly on central motor neural circuits, several other studies have shown some level of stimulus localization with larger transducers and higher ultrasound frequencies, suggesting that smaller focal spots may result in direct neuromodulation effects with superior targeting specificity (Li et al, 2016, Kamimura et al, 2016. Further work is needed to determine more precisely which central motor neural circuits are being directly activated by ultrasound, perhaps using implanted EEG or cranial window whole brain measuring techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, adding further weight to the idea that US stimulation acts directly on central motor neural circuits, several other studies have shown some level of stimulus localization with larger transducers and higher ultrasound frequencies, suggesting that smaller focal spots may result in direct neuromodulation effects with superior targeting specificity (Li et al, 2016, Kamimura et al, 2016. Further work is needed to determine more precisely which central motor neural circuits are being directly activated by ultrasound, perhaps using implanted EEG or cranial window whole brain measuring techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial ultrasound stimulation in rodents has resulted in motor responses such as whole body twitches (Tufail et al, 2010, King et al, 2013, Ye et al, 2016. There also is evidence that ultrasound can be applied to modulate region-specific brain activity in rabbits and to induce lateralized motor responses in mice (Kamimura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…13,17, 22,34 The current surge of interest in it as a noninvasive neurostimulation modality has been triggered by the following relatively recent findings: 1) FUS can elicit neuromodulatory effects in the CNS by using relatively short stimuli; 59 2) short stimuli of low intensity can trigger visible movements upon motor cortex stimulation in rodents; 2527,35,38, 56,62 and 3) the method has been safely used in primates, including humans. 9,21,3234,60 Given the enormous potential of this neurostimulation modality in causal brain mapping and treatments of deep brain circuits, work is currently under way to provide the information necessary for effective use.…”
Section: Transcranial Focused Ultrasoundmentioning
confidence: 99%
“…superior colliculus, pretectal nucleus, and hippocampus etc. with 1.9 MHz focused ultrasound (PRF: 1 kHz, Duty cycle: 50%, lateral focus 1.0 mm, axial focus 8.5 mm), reproducibly inducing eyeball movement and pupillary dilation [38]. The improved spatial specificity produced by the increased FF was demonstrated to lead to consistent behavioral responses compared to lower FF scenarios [38].…”
Section: Tfus Directly Activates Local Brain Tissuementioning
confidence: 99%